Caracterização morfocultural e molecular de Colletotrichum spp. associados a antracnose em manga, mamão e goiaba - Stracieri, Juliana [UNESP] (2015)
Brazil ranks third among the largest fruit producers in the world with more than 40 million tons per year and a planted area of about three million hectares. However, this sector has complex problems of different nature, such as plant diseases and among them, anthracnose. This disease is caused by fungi of the Colletotrichum genus. Losses resulting from this disease happen pre- and post-harvest, reaching 90% of damage depending on environmental conditions and management adopted. Colletotrichum gloeosporioides is described most often as the causal agent of anthracnose in tropical fruits; however, recent studies have shown that this is not always the case. In general, the pathogens described in connection with the complex symptoms of anthracnose in fruits are classified either as Colletotrichum gloeosporioides or Colletotrichum acutatum. But, recent studies have shown that the criteria adopted to classify the pathogen species associated with the symptoms are not always the most appropriate. Thus, simultaneous analysis of morphocultural and molecular characteristics are necessary to classify these pathogen species more accurately